Answer :

6 = (m1y2 + m2y1)/ m1 + m2


6 = (m1 × 8 + m2 3)/ m1 + m2


6 = (8m1 + 3m2 ) / m1 + m2


8m1 + 8m2 = 6(m1 + m2)


2m1 – 3m2 = 0


m1:m2 = 3:2


Now,


m = (m1x2 + m2x1)/ m1 + m2


m = (m1 × 2 + m2 (– 4))/ m1 + m2


m = (2m1 – 4m2 ) / m1 + m2


2m1 – 4m2 = m(m1 + m2 )


Putting the values of m1 & m2


m = – 2/5


Hence, 3:2, m = – 2/5


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses